2023
DOI: 10.1111/padr.12530
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health Trajectories of Norwegian Parents and Children before and after Union Dissolution

Abstract: The aim was to examine the mental and physical health trajectories of mothers, fathers, and children before and after union dissolution. Register data covering the entire Norwegian population, and including information on consultations with general practitioners in 2006–2018, were used. Constant unobserved characteristics were controlled for with individual fixed effects. As judged by the number of consultations, mothers’ and fathers’ mental health deteriorates before the dissolution but improves immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Divorce is a stressful event which might cause mental and psychosomatic disorders, either in the short term or more permanently. While some studies have shown that mental distress increases during the last years preceding the partnership dissolution and declines after the break-up (Blekesaune, 2008 ; Ding et al, 2021 ; Kravdal & Wörn, 2023 ; Leopold, 2018 ; Van Scheppingen & Leopold, 2020 ), other studies have indicated more long term adverse health consequences of divorce on measures such as contact with primary healthcare services for mental health problems (Reneflot et al, 2020 ), mental distress (Mastekaasa, 1995 ), immune functioning (Kiecolt-Glaser et al, 1987 ) and physical illness (Kravdal & Wörn, 2023 ; Lorenz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Divorce is a stressful event which might cause mental and psychosomatic disorders, either in the short term or more permanently. While some studies have shown that mental distress increases during the last years preceding the partnership dissolution and declines after the break-up (Blekesaune, 2008 ; Ding et al, 2021 ; Kravdal & Wörn, 2023 ; Leopold, 2018 ; Van Scheppingen & Leopold, 2020 ), other studies have indicated more long term adverse health consequences of divorce on measures such as contact with primary healthcare services for mental health problems (Reneflot et al, 2020 ), mental distress (Mastekaasa, 1995 ), immune functioning (Kiecolt-Glaser et al, 1987 ) and physical illness (Kravdal & Wörn, 2023 ; Lorenz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of the association between union status and health have controlled for constant unobserved individual characteristics in an individual fixed effects analysis, but that requires repeated measurement of health outcomes (such as the annual number of consultations with general practitioners, as in the studies by Kravdal and Wörn ( 2023 ) and Kravdal et al ( 2022 )). Another approach could be to control even better than we have done for genetic selection and family environment by employing information on twins (not adequately available in our data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,23,24 The association between experiencing a stressful life event and mental health is strongest around the time that the event occurred. [40][41][42] Consequently, the moderating effect of partnership status on genetic susceptibility to depression might depend on the relationship quality, relationship duration and time since partnership status change. Future research might benefit from combining structural and subjective indicators for social relationships and investigating possible anticipation and adaptation effects of partnership status transitions to assess the moderating effect of social relationships on the genetic susceptibility to depression.…”
Section: Discussionmentioning
confidence: 99%
“…First, reverse causality may occur, with parental separation leading to child physical health conditions. For example, changes in child health following parental separation have been observed by Kravdal and Wörn (2023). Second, the health condition could be endogenous and caused by factors that increase the risk of both separation and developing childhood health conditions (i.e., confounding variables), such as a lack of financial resources (Doyle, Harmon, and Walker 2005).…”
Section: Parental Separation Risk Preceding a Child Health Condition ...mentioning
confidence: 99%